VALIDITAS PERANGKAT PEMBELAJARAN IPA BERBASIS ETNOSAINS UNTUK PENGUATAN MODERASI BERAGAMA DI SMA KELAS X - Arman Kalean (Al-Alam: Islamic Science Education Journal, 2025)
Strengthening religious moderation in senior high schools is a strategic necessity in addressing the dynamics of Indonesia’s diverse society, particularly in the archipelagic regions with high social and cultural diversity. One approach to instilling values of religious moderation is through the development of contextual learning materials rooted in local wisdom. Ethno-science, as an integration of modern scientific knowledge and local wisdom, has the potential to create meaningful learning experiences while fostering moderate attitudes among students. This study aims to develop and assess the feasibility of ethno-science-based science learning materials integrated with religious moderation values for 10th-grade students in senior high schools. The study employed a research and development (R&D) design, limited to the planning, design, and formative evaluation stages through expert validation, referring to Kemp’s instructional design model. The developed products included Lesson Plans (RPP), Student Worksheets (LKPD), and Learning Outcome Assessment Sheets (LP-THB). Feasibility was assessed by content, instructional, and language experts using validation instruments analyzed descriptively and quantitatively. The results showed that the RPP received an average score of 3.53 (valid category), LKPD scored 3.46 (valid category), and LP-THB scored 3.76 (very valid category). The reliability of the three instruments was high: 96.52% for RPP, 89.40% for LKPD, and 95.08% for LP-THB. These findings indicate that the developed ethno-science-based learning materials are theoretically feasible for use in 10th-grade science instruction after revisions based on expert feedback. This study confirms that ethno-science-based instructional development has the potential to serve as an alternative learning design that not only enhances science education quality but also supports the strengthening of religious moderation. However, this study is limited to expert validation and has not yet proceeded to classroom implementation or effectiveness testing.